(untitled) (CIPEEX, 2022)
FIBROMYALGIA (FM) IS A CHRONIC PAIN SYNDROME CHARACTERIZED BY GENERALIZED MUSCULOSKELETAL PAIN, USUALLY ASSOCIATED WITH TIREDNESS, FATIGUE AND SLEEP DISORDERS. THEREFORE, THIS INTEGRATIVE REVIEW AIMS TO ANALYZE THE STUDIES THAT INTERRELATE THE EATING PATTERN AND&NBSP;FIBROMYALGIA. THIS IS A MINI INTEGRATIVE LITERATURE REVIEW STUDY WITH ARTICLES SELECTED FROM THE BIBLIOTECA VIRTUAL EM SAÚDE (BVS) AND PUBMED PORTAL THAT ANSWER THE GUIDING QUESTION: WHAT ARE THE ASSOCIATIONS BETWEEN CHRONIC PAIN, DIET AND HEALTH OF ADULTS WITH FIBROMYALGIA? IN THIS MINI INTEGRATIVE REVIEW, IT WAS ANALYZED 5 ARTICLES THAT PRELIMINARILY MET THE INCLUSION CRITERIA AND WERE IN LINE WITH THE OBJECTIVE OF FIND A POSSIBLE INTERFERENCE OF THE EATING PATTERN IN FIBROMYALGIA. THAT BEING SAID, IT IS CLEAR THAT A BALANCED DIET AND ADEQUATE SUPPLEMENTATION, ACCORDING TO EACH SPECIFIC NEED OF THE PATIENT AND WITH THE EVIDENCE IN THE LITERATURE, WORK AS FACTORS TO IMPROVE&NBSP;FIBROMYALGIA.